Heat shock and salicylic acid on postharvest preservation of organic strawberries - Coltro, Sidiane (2014)
Heat shock and salicylic acid have been studied on shelf-life extension of fruits. The benefits of these techniques have been related to their effect on inducing physiological defense responses against the oxidative stress and pathogen development. The objective of this study was to evaluate the effect of heat shock and salicylic acid on the postharvest preservation and contents of total phenolics, anthocyanins, ascorbic acid, fresh weight loss and microbiological quality of organic strawberries cv. Dover. Strawberries produced organically and stored at 5 ºC were subjected to heat shock (45 ºC ± 3 ºC for 3 h), application of salicylic acid (soaking in 2.0 mmol L^-1 solution), heat shock in combination with salicylic acid and control. After treatment, the fruits were packed and stored in a climatic chamber at 5 ºC ± 2 ºC. At 1, 7 and 14 days, the experimental units were removed from refrigeration and kept at room temperature of approximately 20 ºC for two days. There was no effect of treatments on fresh weight loss, incidence of pathogens or chemical variations in strawberry fruits during the storage period. In natural conditions, organically grown strawberries remained in good condition for sale up to seven days of storage in all treatments.